2021
DOI: 10.1039/d0se01611j
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of bi-layer cathode materials with experimentally validated parameters to improve ion diffusion and discharge capacity

Abstract: Simulation shows that higher electrode utilization (next to current collector) and first discharge capacity can be achieved at high C-rates with bi-layer design compare to conventional electrodes, alongside an increase in energy-power density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 64 publications
2
17
0
Order By: Relevance
“…The average particle diameter for big and small particles are ~ 10µm and ~1µm respectively, confirmed by statistical image analysis. A similar PSD was observed in our previous work on NMC811 [27]. The BET surface area of the milled powder sample is .…”
Section: Particle Morphology Of Processed Materialssupporting
confidence: 87%
See 2 more Smart Citations
“…The average particle diameter for big and small particles are ~ 10µm and ~1µm respectively, confirmed by statistical image analysis. A similar PSD was observed in our previous work on NMC811 [27]. The BET surface area of the milled powder sample is .…”
Section: Particle Morphology Of Processed Materialssupporting
confidence: 87%
“…The electrode slurries with small and big particles were dried in an oven at 70° C and 80° C respectively for 10 hours. The further description of the slurry mixing process, single layer electrode fabrication process, and the justification of choosing certain slurry compositions can be found in our previous work on LiNi 0.8 Mn 0.1 Co 0.1 O 2 (NMC811) [27]. A recent study has revealed that Ni-rich NMC811 is prone to surface contamination during electrode processing because of its high surface reactivity under ambient air exposure, leading to rapid capacity fade [31].…”
Section: Materials Processing and Bi-layer Electrode Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…These mechanisms lead to an increase in the reaction rate-the number of reactions per unit time-which causes an increase in the potential on the galvanostatic curve. Similar processes occur in [18], where for an inorganic material with smaller particles, the discharge curve is formed at relatively higher potentials and the efficiency of reactions increases. On the other hand, there is an additional increase in surface energy due to the addition of lithium ions to the structure, which in turn leads to a decrease in the energy difference before and after the introduction of lithium [21].…”
Section: Electrochemical Activitymentioning
confidence: 65%
“…As a result of the discharge at the cathode/electrolyte interface, the concentration of lithium cations whose penetration into the cathode volume is limited by the mass transfer of the interface and the diffusion coefficient increases. The interaction of lithium ions with the interface and the presence of electrolyte anions can cause a number of undesirable surface reactions that will cause the formation of a passivating film on the cathode surface [17][18][19], which will complicate the further transport of lithium ions. The contribution of such a layer will be reflected in the impedance in the form of an increase in the semicircle responsible for the boundary resistance.…”
Section: Electrochemical Activitymentioning
confidence: 99%